Latitudinal GRBR_TEC estimation in Southeast Asia region based on the two_station method - Kornyanat Watthanasangmechai; Mamoru Yamamoto; Akinori Saito; Takuya Tsugawa; Tatsuhiro Yokoyama; Pornchai Supnithi; Clara Yono Yatini (My University, 2014)
Abstract Total electron content (TEC) is an important parameter for revealing latitudinal ionospheric structures, such as the equatorial ionization anomaly (EIA) in Southeast Asia. Understanding the EIA is beneficial for studying equatorial spread F . To reveal the structures, the absolute TEC as a function of latitude must be accurately determined. In early 2012, we expanded a GNU Radio Beacon Receiver (GRBR) network to provide latitudinal coverage in the Thailand‐Indonesia sector. We employed the GRBR network to receive VHF and UHF signals from polar low‐Earth‐orbit satellites. The TEC offset is an unknown parameter in the absolute TEC estimation process. We propose a new technique based on the two‐station method to estimate the offset for the latitudinal TEC estimation, and it works better than the original method for a sparse network. The TEC estimation system requires two iterations to minimize the root‐mean‐square error (RMSE). Once the RMSE reaches the global minimum, the absolute TECs are estimated simultaneously over five GRBR stations. GPS‐TECs from local stations are used as the initial guess of the offset estimation. The height of the ionospheric pierce point is determined from the ionosonde hmF2. As a result, the latitudinal GRBR‐TEC was successfully estimated from the polar orbit satellites. The two EIA humps were clearly captured by the GRBR‐TEC. The result was well verified with the TEC reconstructed from the C/NOFS density data and the ionosonde bottomside data. This is a significant step showing that the GRBR is a useful tool for the study of low‐latitude ionospheric features.
Keywords: Ionosonde; Precise Point Positioning; Ionosphere and magnetosphere dynamics